What Do We Have When We Have a Narrative?. (December 2017) - Grysman, Azriel; Mansfield, Cade D.
This review introduces our special issue, which presents a variety of papers with explicit assumptions of how narrative methods are used in cognitive and personality psychology studies of autobiographical narratives. We begin this review with an examination of how narrative is conceptualized in terms of reflecting and influencing a sense of self that is sculpted via social interaction. After explicating these constructs more carefully, we turn to an analysis of narrative methods, examining how different methodologies of narrative coding take on certain assumptions, either implicitly or explicitly, regarding narrative, self, and social interaction.